Corruption in Russia - Historic Legacy and Systemic Nature - Günther G. Schulze; Nikita Zakharov (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper argues that corruption in Russia is systemic in nature. Low wage levels of public officials provide strong incentives to engage in corruption. As corruption is illegal, corrupt officials can be exposed any time, which enforces loyalty towards the powers that be; thus corruption is a method of governance. We trace the systemic corruption back to the Mongolian empire and demonstrate its persistence to the current regime. We show the geographic distribution of contemporary corruption within Russia, survey the literature on the causes, consequences, and cures of corruption in Russia, and discuss entry points to fighting it.
Keywords: D73; H11; H73; K42; N40; P37; 330; corruption; governance; institutions; political economy; history; Russia